Brain metabolic correlates of fatigue in Parkinson's disease: a PET study. (3rd April 2018) - Zhang, Li; Li, Tiannv; Yuan, Yongsheng; Tong, Qing; Jiang, Siming; Wang, Min; Wang, Jianwei; Ding, Jian; Xu, Qinrong; Zhang, Kezhong
ABSTRACT: Purpose: The neural bases of fatigue in Parkinson's disease (PD) remain uncertain. We aimed to assess the brain metabolic correlates of fatigue in patients with PD. Patients and methods: Twenty-seven PD patients without clinically relevant depression (17-item Hamilton Depression Rating Scale (HAMD) score ≥ 14), apathy (Apathy Scale (AS) score ≥ 14) and excessive daytime somnolence (Epworth Sleepiness Scale (ESS) score ≥ 10) were evaluated with Fatigue Severity Scale (FSS). Each patient had an F-18 fluorodeoxyglucose positron emission tomography (FDG-PET) scan. Motor symptoms were measured with the Unified Parkinson's Disease Rating Scale motor part. Levodopa equivalent daily dose for each patient was also calculated. The PET images were analyzed using statistical parametric mapping software. We introduced the age, educational level, HAMD scores, AS scores and ESS scores as covariates. Results: High FSS scores were associated with brain hypermetabolism in areas including the right middle temporal gyrus (Brodmann area (BA) 37) and left middle occipital gyrus (BA 19). Increased FSS scores correlated with hypometabolism in regions such as the right precuneus (BA 23), left inferior frontal gyrus (BA 45) and left superior frontal gyrus (orbital part, BA 11). Conclusion: This study demonstrates that brain areas including frontal, temporal and parietal regions indicative of emotion, motivation and cognitive functions are involved in fatigue in PD patients.